Microextração líquido-líquido dispersiva em fase reversa assistida por vórtex para determinação de Fe, Mg e Zn em óleos vegetais por espectrometria de absorção atômica - Reis, Priscila Karachinski dos (2018)
In this work, Vortex-assisted reverse-dispersive liquid-liquid dispersion (RP-DLLME) is proposed for the preparation of oil samples and for further determination of metal species by flame atomization (F AAS) atomic absorption spectrometry. RP-DLLME was proposed using 2-propanol and nitric acid solution (HNO3) as dispersant and extractor solvents, respectively. The following parameters were optimized: type and volume of dispersing solvent, acid concentration in the extracting solvent and ultrasonic time. Under optimized conditions, 5 g of the samples were heated (at a temperature of 95 ± 5 ° C) for 10 min, then added with 1 ml of the solvent mixture, 2- propanol and 1% HNO3 solution (v/v), vortexed for 20 sec if sonicated in an ultrasonic bath for 10 min. After RP-DLLME, the supernatant was separated by centrifugation and the concentrations of Fe, Mg and Zn in the extractive phase were determined by F AAS. Calibration was performed by RP-DLLME using addition of organometallic standards in previously purified vegetable oil sample. The calibration intervals were 0.05-0.50 μg g-1 , 0.01-0.10 μg g-1 and 0.02-0.20 μg g -1 for Fe, Mg and Zn respectively. The limit of detection (LOD) values were 9 ng g-1 , 2 ng g-1 and 8 ng g-1 for Fe, Mg and Zn. The relative standard deviation (RSD) values obtained were between 1 and 11%. The comparison of the results obtained by the proposed methodology with those obtained by direct dilution did not show a significant difference by paired test T and test F. The recovery tests showed values between 81-110%, demonstrating the good accuracy of the method. The proposed method was applied for the determination of Fe, Mg and Zn in samples of vegetable oils of different origins, and the concentrations obtained were of the order of μg g-1 .